QUALITY CONTROL ASSESSMENT OF DIFFERENT BRANDS OF CIPROFLOXACIN 500 MG TABLETS IN YEMEN - Alyahawi, Ali; Alsaifi, Abdulmajed (Universal Journal of Pharmaceutical Research, 2018)
Objective: Ciprofloxacin is a fluorinated 4-quinolone or fluoroquinolone antibacterial with a wider spectrum of activity than nalidixic acid and more favorable pharmacokinetics allowing its use in systemic infections. It has been used in the treatment of a wide range of infections. Many different brands and dosage forms of Ciprofloxacin hydrochloride are available in the Sana'a market that places health practitioners in a dilemma of drug substitution in case of non-availability of a particular brand. The aim of the present study was to evaluate the quality control of five brands of Ciprofloxacin hydrochloride tablets marketed and commonly prescribed in Sana'a city. The results and findings of the present study will be interpreted and discussed. Methods: Five brands of Ciprofloxacin hydrochloride tablets (500 mg) were purchased from the retail pharmacy outlets and their pharmaceutical quality were assessed by using in-vitro tests as per the British Pharmacopoeia (BP) and unofficial standards as recommended by the manufacturers. The assessment of tablets included the evaluation of uniformity of weight, friability, hardens, disintegration time, dissolution test and assay content by UV spectrophotometric method. Results: All brands passed USP and BP standards in- vitro quality control tests prescribed for the tablets except hardens test but the all products were satisfactory for hardness. Conclusion: The results indicated that the overall quality of all tested Ciprofloxacin hydrochloride tablets brands was satisfactory as they met the requirements of the official and unofficial quality control tests. Peer Review History: Received 6 June 2018; Revised 11 July; Accepted 13 August; Available online 15 September 2018 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Ali Abdullah A. Al-Mehdar , University of Basrah, Iraq, asia_abdullah65@yahoo.com Dr. Ahmad Abdelsattar El-Ebiary , Tanta University Hospitals, Tanta, Egypt, a.ebiary@med.tanta.edu.eg